Amide rotation trajectories probed by symmetry12. Issue 32 (2nd August 2017) - Kubyshkin, Vladimir; Budisa, Nediljko
Abstract : Here we utilized symmetric proline analogues in order to mimic trajectories of the amide rotation and characterize differences in the rotation scenarios. Abstract : Amide rotation of peptidyl–prolyl fragments is an important factor in backbone structure organization of proteins. Computational studies have indicated that this rotation preferentially proceeds through a defined transition-state structure ( syn / exo ). Here, we complement the computational findings by determining the amide bond rotation barriers for derivatives of the two symmetric proline analogues, meso and racemic pyrrolidine-2, 5-dicarboxylic acids. The rotations around these residues represent syn / exo – syn / exo and anti / endo – syn / exo hybrid transition states for the meso and racemic diastereomer, respectively. The rotation barriers are lower for the former rotation by about 9 kJ mol −1 (aqueous medium), suggesting a strong preference for the syn / exo (clockwise) rotation over the anti / endo (anticlockwise) rotation. The results show that both hybrid rotation processes are enthalpically driven but respond differently to solvent polarity changes due to the different transition state dipole–dipole interactions.